Development of water resources in India - Garg, Vikas; Singh, V. P.; Raj, Vijay (Springer, 2017)
This proceedings volume, with more than 30 chapters, is based on the presentations given at the National Conference on Water Resources and Hydropower (WRHP-2016) and represents the state-of-the-art in water resources in India. It includes experimental investigations, field studies, theoretical developments, numerical methods, as well as engineering achievements in water resources. The contributions are organised under four main topics: " Water Resources and Management: covers the issues related to water resources planning and management, water conservation, flood mitigation, policies and governance, conflict over rivers and planning of groundwater evolution, Assessment of Sedimentation, Surface water quality, Rainfall assessment, " Climate Change and Global Warming: includes chapters on the impact of climate on water resources and groundwater, hydrological impacts of climate change, Ground Water Contaminants, Assessment of Evaporation and evapotranspiration effects on global warming " Hydraulic Structures: presents contributions on fluvial hydraulics, flow through Weirs, Open Channel flow, river flood control, scour and erosion, dam and dowstream block failures and protection, Losses in pipes By combining these topics, the book provides a valuable resource for practitioners and researchers, including field engineers, academicians, planners, health specialists, disaster managers, decision makers and policy makers engaged in various aspects of water resources and hydropower. The WRHP-2016 was organised in association with the Indian Institute of Technology, Roorkee, Uttrakhand Jal Vidyut Nigam Limited and the Indian Society for Hydraulics, Pune and was held in University of Petroleum and Energy Studies, Dehradun, India from June 17-18, 2016.
Keywords: Water resources development -- India -- Congresses.; India.; elektronické knihy; electronic books